Incoherent color holography lattice light-sheet for subcellular imaging of dynamic structures - Alford, Simon; Mann, Christopher; Art, Jonathan; Potcoava, Mariana (Frontiers in Photonics, 2023)
The purpose of the article is to explore the need and advantages of using the incoherent color holography lattice light-sheet (ICHLLS) to provide multiwavelength quantitative monitoring of 3D cellular dynamics in live tissue to further understand complex functions of cells and cellular compartments. We have explored the use of incoherent color holography lattice light-sheet to investigate colocalization of fluorescent markers in live cells in intact tissue. Neuronal structures provide an attractive target for incoherent color holography lattice light-sheet. The cells show a complex architecture in 3D space in which signaling both between cells and within subcellular structures requires colocalization of proteins and lipids to function. During activity and over long periods it is important in understanding these signaling functions in Parkinson’s, Alzheimer’s and motoneuron diseases within live cells in intact tissue. As a proof of concept this article recalls the key aspects in lattice light-sheet imaging and provides a description of the incoherent detection system configuration to actively control dual diffractive lenses phase-shifting at multiple excitation wavelengths sequentially, and per each z-galvo scanning level, with extended field-of-view. The incoherent color holography lattice light-sheet system will allow simultaneous recording of multidimensional object waves that contain intensity in 3D space, phase, and wavelength information. We measure colocalization of fluorescence indicators introduced into live cells in intact neural tissue.